A night to remember – the Society’s winter dinner - Tasfia Hazari (BioScientist: The Salford Biomedicine Society Magazine, 2024)
The Salford Biomedicine Society culminated 2023 with a dinner event, bringing members together to celebrate what has been a fantastic year! President of the Biomedicine Society, Tasfia Hazari, reflects on this event and tells us what it was like to organise and attend this unmissable event.